2021
DOI: 10.1101/2021.06.21.21258543
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Long Term Health Consequences of COVID-19 in Hospitalized Patients from North India: A follow up study of upto 12 months

Abstract: Purpose: Long COVID syndrome is now a real and pressing public health concern. We cannot reliably predict who will recover quickly or suffer with mild debilitating long COVID 19 symptoms or battle life threatening complications. In order to address some of these questions, we studied the presence of symptoms and various correlates in COVID 19 patients who were discharged from hospital, 3 months and up to 12 months after acute COVID 19 illness. Methods: This is an observational follow up study of RT PCR confirm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Diabetes mellitus (37%) was the most common comorbidity followed by systemic hypertension (30.8%). The same was reported by Budhiraja et al [ 22 ], Garrigues et al [ 23 ], Sykes et al [ 24 ], and Fatima et al [ 25 ]. But in the studies by Halpin et al [ 26 ], Peghin et al [ 27 ], Iqbal et al [ 28 ], and Todt et al [ 18 ], the prevalence of systemic hypertension was more compared to type 2 diabetes mellitus.…”
Section: Discussionsupporting
confidence: 85%
“…Diabetes mellitus (37%) was the most common comorbidity followed by systemic hypertension (30.8%). The same was reported by Budhiraja et al [ 22 ], Garrigues et al [ 23 ], Sykes et al [ 24 ], and Fatima et al [ 25 ]. But in the studies by Halpin et al [ 26 ], Peghin et al [ 27 ], Iqbal et al [ 28 ], and Todt et al [ 18 ], the prevalence of systemic hypertension was more compared to type 2 diabetes mellitus.…”
Section: Discussionsupporting
confidence: 85%
“…These estimates are similar to a study from India published in pre-print server, which reported dyspnea in 74.3% and fatigue and disturbed sleep in more than 50% of patients after 30 to 40 days of recovery [ 26 ]. Another study in pre-print, which estimated Long COVID in hospitalized patients of North India, gave an estimate of 40.3% after 4 to 6 weeks follow-up [ 27 ]. High prevalence of Long COVID symptoms in severe and hospitalized cases are reported from multiple studies from all over the world [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…We screened 9768 results from de-duplicated retrieved records to populate our evidence map. After excluding those that focused on adults and those not meeting our eligibility criteria for this review, we identified 25 studies, including over 68 thousand children and adolescents (this is an estimate since case-mix studies did not provide the exact number; see Table 1 for a summary of the main characteristics and Figure 1 for a PRISMA flow chart and see our OSF project page for the full details of the excluded studies) [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ]. Most studies were available as journal articles (all in English), 84% had a longitudinal design, and six had a control group [ 7 , 23 , 29 , 30 , 39 , 41 , 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…Five studies reported this outcome [ 26 , 29 , 34 , 36 , 40 ]. The LongCOVIDKidsDK controlled study indicated that 695 adolescents (10.5%) of those who tested positive for COVID-19 reported 16 or more days of school absence and poorer quality of life associated with school functioning (see Table 2 and section below on controlled studies) [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation